Parques urbanos: subsídios para a elaboração de instrumentos de gestão - Pinheiro, Raquel Reia (Universidade Federal de São Carlos, 2021)
Facing global climate challenges and the search for sustainable development, the creation of parks in urban areas has become a strategy to deal with these issues. Among the green areas of cities, the Urban Park is a category that has multiple benefits and functions. Therefore, instruments that aim for a better planning and management of these places are extremely relevant. Widely spread within the Conservation Units (UCs) context, the Management Plans aim to provide relevant information about the managed location, the zoning of the area, the rules of use, instructions for the management of natural resources, among other guidelines. In the city of São Paulo-SP, the “Master Plans for Municipal Urban Parks” also aim to delimit and provide fundamental guidelines for the management of these places. The mentioned contexts suggest that the search for relevant characteristics of these instruments can be useful in the construction of management documents for urban parks in general. Therefore, the objective of this research is to present subsidies for the elaboration of management instruments for urban parks. From the analysis of Methodological Guidelines for the Elaboration of Management Plans, proposed by ICMBio and by the São Paulo Environmental System, it was possible to list elements that could possibly guide the formulation of instruments focused in urban parks. Management Plans and Master Plans of Urban Parks in areas located in the city of São Paulo-SP were also analyzed and allowed the observation of factors that can be incorporated into the management of urban parks and aspects that can contribute to the development of similar instruments in other cities. The results obtained indicate that management instruments for urban parks should be designed and structured taking into account the characteristics of the area and its surroundings, promoting shared management, delimiting zones to ensure compatible uses, identifying programs and actions, defining administrative procedures and management, as well through constant monitoring to promote the adaptive management of these places.
Urban parks: subsidies for the development of management instruments
Keywords: Manejo de parques urbanos; Gestão pública; Instrumentos de planejamento urbano; Urban park management; Public management; Urban planning instruments; CIENCIAS AGRARIAS::AGRONOMIA::FLORICULTURA, PARQUES E JARDINS; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::METODOS E TECNICAS DO PLANEJAMENTO URBANO E REGIONAL